Syntheses of novel N-confused porphyrins bearing amino and carboxylic acid functional groups - Dela Rosa, Mira Anne C.
Iron (II) complexes of N-confused tetraphenylporphyrin (NCTPP) have been reported to react with S-nitrosothiols forming an iron nitrosyl complex with the sulfur atom inserted in the Fe-C bond. Hence the possibility of using NCTPP as a probe for S-nitrosylation in proteins has become apparent. However, NCTPP is poorly soluble in biological medium such that the derivatization of NCTPP to include a site for attachment of water soluble nanoparticles is being explored. In line with this, NCTPP is being derivatized with amino and carboxylic acid functional groups and in this work, substituted N-confused porphyrins bearing amino or carboxylic acid groups were synthesized.